Successful Periapical Lesion Healing without Root Canal Obturation Associated with Photodynamic Therapy: A Case Report: Journal of Lasers in Medical Sciences. 2025;16 3Unusual healing of a periapical lesion without root canal obturation - Zargar, Nazanin; Nasrabadi, Navid; Hemmati, Ghazal; Asgari, Mohadeseh (Journal of Lasers in Medical Sciences, 2025)
Introduction: Total bacterial disinfection in root canal therapy is challenging due to residual infected dentin, which may harbor bacteria. Photodynamic therapy (PDT) enhances antibacterial efficacy and supplements conventional endodontic treatment. Case Presentation: This case report describes the healing of a large periapical lesion in a 22-year-old male patient with pulp necrosis and a secondary acute apical abscess in the mandibular left incisors. The patient underwent cleaning and shaping of the root canal system, but did not return for obturation. After chemo-mechanical reparation and calcium hydroxide dressing, the patient received PDT using 0.1 mg/mL Toluidine Blue (FotoSan®; CMS Dental, Denmark) and an LED lamp (630 nm, 3 W/cm²). Despite the absence of root canal obturation and delayed treatment, radiographic examination at the 1-year follow-up showed complete healing of the periapical lesion with no symptoms. Conclusion: This unexpected outcome suggests that PDT may improve disinfection and lead to successful treatment even without conventional root canal obturation. PDT, when combined with conventional root canal therapy, may enhance treatment outcomes